Introduction to Online Learning and It’S Scope In Education System: Exploring the Various Terms and Tools of Online Learning (Journal of Advances and Scholarly Researches in Allied Education, 2012)
INTRODUCTIONTO ONLINE LEARNING Oneof the difficulties in gaining a clear sense of literature on online learningis the multiplicity of terms used to represent the phenomenon. Commonly usedterms are distributed learning, distance learning, online learning, e-learningand computer mediated learning. Online learning refers to learning and othersupportive resources that are possible through a computer. Online learning alsoknown as e-learning is the process of engaging in learning through the use ofelectronic technology. It consists of the use of computer programs, CD-ROMs,online puzzles, computer quizzes, learning quests, researching online, bulletinboards, online discussions, DVDs, online streaming and television. In an onlinelesson the computer displays material in response to the request of a learner.The computer prompts the learner for several information and presents propermaterial concerned on the response of learner. The material can be as easy aslessons from a classroom course and supplement tests that are typewritten intoa computer program or as complex as a program that tracks user input andsuggests proper learning material. It can be a work session that exists oncomputer in which case the learning is a byproduct of the experience or it canbe configured for needs other than learning in which the learners go through itwith the aim of acquiring specific content. Several software companies claimsto be electronic learning specialists. The outcomes of electronic are no variedfrom conventional learning results needed by teachers in tasks of offline classroom.The material can be represented as graphics, text, audio, video, animatedgraphics or a combination of any of these. Some institutions of education begintheir commands as training students who are dispersed geographically from theinstitution and from one another themselves. They denote what has been referredto as distance education (Carliner, 2004, p 1-4; Bowman, 2010).